MANAJEMEN KEAMANAN CYBER DI PERUSAHAAN - Yesta Sadha Saputra; Rizki Nur Wakhid, Raihan Gading Rabbani, Ammar Wildan, Arif Bentar Suganda Heriyanto,Tubagus Hedi Sa (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Cyber security has become an increasingly important issue in the era of modern technology. In recent years, we have seen an increase in the number and complexity of cyber attacks that threaten computer systems and data around the world. Attacks such as data theft, malware attacks, hacking, and DDoS attacks have resulted in financial losses, imagery, and business operations. The chosen qualitative approach allows researchers to explore subtle and complex aspects of complex situations such as corporate security and security management. The objective of this qualitatively descriptive research is to gain a deeper understanding of how effective security management affects corporate safety. It can undermine customer confidence, brand value, and relationships with business partners and other stakeholders. Therefore, security management should take proactive action to avoid security issues that could damage the Company's reputation